Comparative Study on the Evolution of Airflow Temperature and Valid Ventilation Distance Under Different Cooling Strategies in High-Temperature Tunnels for Mining Thermal Energy - Fangchao Kang; Jinlong Men; Binbin Qin; Guoxi Sun; Ruzhen Chen; Weikang Zhang; Jiamei Chen; Zhenpeng Ye (Fire)
A comprehensive understanding of airflow temperature distribution within high-temperature tunnels is crucial for developing effective cooling strategies that ensure a safe environment and acceptable construction costs. In this paper, we introduce a novel cooling strategy that integrates thermal insulation layers and heat exchangers aligned along the tunnel axis (TIL-HE strategy). We investigate variations in airflow temperature and valid ventilation distance (VVD) and compare them with two other cooling strategies: natural tunnels only employing mechanical ventilation (NT strategy) and tunnels featuring thermal insulation layers (TIL strategy), through the 3D k-ε turbulence model in COMSOL Multiphysics. Our findings indicate that (1) the TIL-HE strategy demonstrates superior cooling performance, resulting in significantly lower airflow temperatures and markedly higher VVD; (2) higher water velocity and more heat exchangers contribute to lower airflow temperature and prolonged VVD; (3) positioning the heat exchangers within the surrounding rock rather than inside the insulation layer leads to even lower airflow temperature and longer VVD. Longitudinal-arranged heat exchangers present fewer construction challenges compared to traditional radial-drilled ones, ultimately reducing tunnel construction costs. These findings provide valuable insights for optimizing cooling strategies and engineering parameters in high-temperature tunnel environments.